CHEMICAL CONSTITUENTS FROM THE ARIAL OF Crinum asiaticum L. - Pham, Van Cong; Ngo, Van Hieu; Ngo, Viet Duc; Vu, Thi Trang; Do, Thi Thu Hien; Do, Thanh Tuan; Nguyen, Thi Thu Hien; Pham, Ngoc Thuat; Nguyen, Tuan Anh; Cu, Lan Huong; và c.s. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Crinum asiaticum L. (locally known Nang hoa trang), belonging to the Crinum genus of the Amaryllidaceae family, has been widely used in oriental and traditional medicine around the world for the treatment of various diseases and exerts diverse promising pharmacological effects. To find out new inhibitors for the treatment of inflammatory and Alzheimer’s diseases, a methanol extract of the aerial part of C. asiaticum was investigated to afford six compounds, chrysophanol (1), emodin (2), physcion (3), thymine (4), thymidine (5), and 5-(hydroxymethyl)-2-furfural (6) by using various chromatographic separations. Their structures were identified by the extensive analysis of 1H- and 13C-NMR data as well as a comparison with those of previously reported data. This is the first report of these compounds (1-6) from C. asiaticum. In addition, all compounds evaluated the inhibitory activities of NO production and acetylcholinesterase (AChE). Among them, emodin (2) significantly inhibited NO production with an IC50 of 5.13±0.42 μM. This result indicated that emodin (2) may be beneficial in the treatment of anti-inflammatory diseases. Besides, all compounds (1-6) also showed weak inhibitory effects on the AChE enzyme with a range of IC50 values from 82.98±9.19 to 237.63±13.8 µM.